Evaluating Quality of Service Design - Hejl, Daniel; Feuerlicht, Jiří; Pavlíčková, Jarmila, 1969-2024; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2011)
Service Oriented Architecture is a popular choice of system architecture and many organization are moving towards it in order to closely align IT capabilities with their business goals. They are expecting that the implementation of SOA will lead to increased efficiency, the ability to rapidly respond to changing business environments, and significantly improved return on investment. In order to meet these expectations, great emphasis must be given on correct service design. However, designing services in the way that they are highly reusable and the final product is highly maintainable can be especially challenging. This bachelor thesis focuses on summarization of how metrics for measuring structural properties of service oriented software designs can be used for predicting potential problems in service design. In the practical part of this thesis, a tool for evaluating a service design based on coupling between service interfaces was implemented and practical applicability of one of the metric was demonstrated.
Vedoucí práce: Jiří Feuerlicht
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2011
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2011
Způsob přístupu: Internet
Keywords: informatika [obor bakal. práce]; bakalářské práce; bachelor's theses